Measurement of Sharing Economy Intention of Bicycle Re-Rent by Students - Laongman, Pacharai; Sintasingha, Purawat (International Journal of Economics and Business Management, 2025)
Based on the experiences and views of consumers using bicycle rental services in Thailand (Amazing Bangkok Cyclist - ABC), this research seeks to explore experiential motivation, customer contentment, and the likelihood of renting again. This study aims to: (a) examine the current use of ABC in colleges in Bangkok, (b) analyze the relationship between experiential motivation, customer satisfaction, and the intent to rent again among ABC users within Bangkok colleges; (c) investigate if experiential motivation, customer satisfaction, and the intention to rent again of ABC users in Bangkok colleges significantly influence one another. In this research, a survey using a questionnaire was carried out. The items were ABC users located on the campus in Bangkok. Statistical analysis was conducted using descriptive analysis, Independent Sample t-test, and Regression Analysis. All findings were evaluated using SPSS statistical software. The findings indicated that: Most ABC users were new students who exercised regularly (approximately one to two times weekly). Most students utilized ABC fewer than 2 times monthly and typically spent under 4 hours biking as a means of short-distance transport. Ultimately, regression analysis was conducted and showed that a significant relationship exists between experiential motivation, customer satisfaction, and the intention to rent again. Consequently, the greater the satisfaction level after cycling, the stronger the motivation to rent again. Ultimately, suggestions were put forward for enhancements in the future